2014
DOI: 10.1089/scd.2013.0307
|View full text |Cite
|
Sign up to set email alerts
|

The Role of CCL5 in the Ability of Adipose Tissue-Derived Mesenchymal Stem Cells to Support Repair of Ischemic Regions

Abstract: Mesenchymal stem cells (MSC) are multipotent and possess high proliferative activity, and thus are thought to be a reliable cell source for cell therapies. Here, we isolated MSC from adult tissues-bone marrow (BM-MSC), dental tissue (DT-MSC), and adipose tissue (AT-MSC)-to compare how autotransplantation of these MSC effectively supports the repair of bone fracture and ischemic tissue. An analysis by in vitro differentiation assays showed no significant difference among these MSC. The degree of calcification a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…Human adipose tissue was obtained after obtaining informed consent from diabetic (n = 3, HbA1c >7.0, longterm treatment) and nondiabetic (n = 3) donors, male, age = 59 -10 years, who were undergoing procedures in the Department of Cardiovascular Surgery, University of Tsukuba Hospital, Tsukuba, Japan. The isolation of AT-MSCs was performed as previously described [24]. Cells were cultured in Iscove's modified Dulbecco's medium (IMDM, 12200-069; Invitrogen), 10% fetal bovine serum, 2 mg/mL Lglutamine (25030; Invitrogen), and 5 ng/mL recombinant human bFGF (064-04541; PeproTech) at 37°C in 5% CO 2 and a humidified atmosphere.…”
Section: The Isolation Of At-mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human adipose tissue was obtained after obtaining informed consent from diabetic (n = 3, HbA1c >7.0, longterm treatment) and nondiabetic (n = 3) donors, male, age = 59 -10 years, who were undergoing procedures in the Department of Cardiovascular Surgery, University of Tsukuba Hospital, Tsukuba, Japan. The isolation of AT-MSCs was performed as previously described [24]. Cells were cultured in Iscove's modified Dulbecco's medium (IMDM, 12200-069; Invitrogen), 10% fetal bovine serum, 2 mg/mL Lglutamine (25030; Invitrogen), and 5 ng/mL recombinant human bFGF (064-04541; PeproTech) at 37°C in 5% CO 2 and a humidified atmosphere.…”
Section: The Isolation Of At-mscsmentioning
confidence: 99%
“…In vitro differentiation was performed as described previously [24]. Osteogenic and adipogenic differentiation were assessed on day 21 by 1% Alizarin Red S (Kodak) and Oil Red O (Muto Pure Chemicals) staining, respectively.…”
Section: The In Vitro Differentiation Of At-mscsmentioning
confidence: 99%
“…We previously found that Alde-Low EPCs were incorporated into newly formed neovessels, indicating that transplanted EPCs contribute to the revascularization of ischemic tissue at the site of the skin flap rather than through the promotion of neoangiogenesis. In the case of mesenchymal stem cells (MSCs), we reported that, in addition to Alde-Low EPCs, transplanted adipose tissue-derived MSCs (AT-MSCs) effectively repaired the perfusion of the blood flow in a mouse model of hindlimb ischemia, indicating that AT-MSC promoted neoangiogenesis through a paracrine mechanism [ 25 ]. The migrated EPCs can secrete SDF-1 themselves to recruit the additional migration of CXCR4-positive EPCs or inflammatory cells to the site of ischemic tissues, suggesting that transplanted and migrated EPCs may function through a paracrine mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Human adipose tissues were collected from the infants (n = 5, 1-12 months) and elderly donors (n = 5, 70-80 years old) who are undergoing the treatment in Department of Cardiovascular Surgery, University of Tsukuba Hospital, Tsukuba, Japan. AT-MSCs were isolated according to a previously described method 44 . In brief, adipose tissues were minced and digested with 0.1% collagenase (Invitrogen, Waltham, Massachusetts, CA, USA) in phosphate-buffered saline (PBS) at 37 °C for 1 h. AT-MSCs were harvested by the centrifugation at 1600 rpm in 7 min, then suspended in the culture medium (Iscove's Modified Dulbecco Medium [IMDM]; Invitrogen), containing 10% heat-inactivated fetal bovine serum (FBS; Invitrogen), 2 mg/ml L-glutamine (Invitrogen), 100 units/ml penicillin (Invitrogen), and 5 ng/ml bFGF (Peprotech, Cranbury, NJ, USA).…”
Section: Isolation and Culture Of At-mscs And Endothelial Progenitor mentioning
confidence: 99%
“…Total RNA from AT-MSCs was isolated using Sepasol-RNA I Super G (Nacalai Testque, Kyoto, Japan) according to the previous described method 44 . In order to synthesize cDNA, a RT-PCR kit (Toyobo Co., Ltd, Osaka, Japan) was used with 1 µg of total RNA.…”
Section: Reverse Transcription-polymerase Chain Reaction (Rt-pcr) Andmentioning
confidence: 99%